2018
DOI: 10.1136/bmjopen-2017-021199
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the rate of publicly financed knee arthroscopies: an analysis of data from the Norwegian patient registry from 2012 to 2016

Abstract: ObjectiveTo examine rates of publicly financed knee arthroscopic surgery in Norway between 2012 and 2016.DesignAnalysis of anonymised data from the National Patient Registry.InterventionsBeginning in 2012, South-Eastern Norway Regional Health Authority implemented administrative measures to bring down rates of knee arthroscopy. Similar measures were not introduced in the other three Regional Health Authorities.Main outcome measuresWe analysed annual national rates of publicly financed knee arthroscopies in 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 27 publications
2
24
0
1
Order By: Relevance
“…We found only a modest 15% decrease in arthroscopies between 2003 and 2017. This was smaller than decreases observed in Florida, where a 23% relative decrease in knee arthroscopy between 2002 and 2015 was found, and Norway, where a 33% decrease between 2012 and 2016 was reported . While arthroscopies decreased from 2008 in Florida, a sustained decline in knee arthroscopy use in Australia was only observed after 2014, more than a decade after the first published placebo‐controlled trial showed arthroscopy was showed arthroscopy for osteoarthritis was of no benefit over placebo …”
Section: Discussionmentioning
confidence: 74%
“…We found only a modest 15% decrease in arthroscopies between 2003 and 2017. This was smaller than decreases observed in Florida, where a 23% relative decrease in knee arthroscopy between 2002 and 2015 was found, and Norway, where a 33% decrease between 2012 and 2016 was reported . While arthroscopies decreased from 2008 in Florida, a sustained decline in knee arthroscopy use in Australia was only observed after 2014, more than a decade after the first published placebo‐controlled trial showed arthroscopy was showed arthroscopy for osteoarthritis was of no benefit over placebo …”
Section: Discussionmentioning
confidence: 74%
“…However, the most recent data do not show a similar decrease in the number of APMs performed 2 12. To further reduce the number of APMs, more effort is needed such as the implementation of administrative measures or (local) policy changes, which were earlier proven to be effective in reducing the number of knee arthroscopies in Norway and Australia 35 36…”
Section: Discussionmentioning
confidence: 99%
“…Variation in preferences are cultural phenomenons, as physicians are quick to adapt their behavior to the enviroment they operate in [26]. Possible approaches to reduce such variation include peer review of practice patterns, such as clinical audits, educational initiatives, development of standardized decision support and leverage of economical incentives, such as the reimbursment per procedure [27]. On the other hand, differences in capacity, such as the number of spine surgeons per population, or surgeons availablity to operating rooms, may cause variation.…”
Section: Discussionmentioning
confidence: 99%